Estradiol/testosterone and estradiol/androstenedione indexes and nutritional status in PCOS women – A pilot study. (November 2019) - Franik, Grzegorz; Maksym, Marta; Owczarek, Aleksander J.; Chudek, Jerzy; Madej, Paweł; Olszanecka-Glinianowicz, Magdalena
Abstract: Objective: The aim of the study was to analyze interrelations between estradiol/testosterone (E2/T) and estradiol/androstenedione (E2/A) indexes and nutritional status, insulin resistance in PCOS. Study design: A cross-sectional study involved 76 PCOS (41 obese) and 67 Non-PCOS (40 obese) women. Anthropometric parameters and body composition were assessed. In fasting state of serum glucose, androgens, estradiol, FSH, LH, SHBG and insulin were measured. E2/T and E2/A indexes and the homeostasis model assessment of insulin resistance (HOMA-IR) were calculated. Results: The values of E2/T and E2/A indexes were significantly lower in the PCOS than Non-PCOS subjects, but did not differ significantly between the obese and normal weight groups. The lowest E2/T and E2/A values were observed in the normal weight PCOS group. Multivariable regression analyses revealed that the presence of PCOS was the major factor affecting both the log10 E2/T (β = −0.16) and log10 E2/A (β = −0.15) indexes. In addition, log10 E2/A index variability was explained by percentage of body fat (β = 0.57). HOMA-IR was not among the explanatory factors in all above models. Comment: The E2/A index is more affected by nutritional status than E2/T index. The lower value of both indices in PCOS women with normal body mass suggest that aromatase activity in PCOS are related to nutritional status.